Paley’s Principle: What Do Sceptics of Testimony Owe? - Kenyon, Tim (Informal Logic, 2025)
William Paley objects to David Hume’s rejection of miracle testimony, and especially Hume’s seeming conviction that, as Paley puts it, “we are not obliged to explain how the story of the evidence arose” when confronted with testimonial evidence for claims that we reject as incredible. Paley holds that it is in some sense insufficient to dismiss miracle testimony merely with the claim that it must, somehow or other, be mistaken. Rather, we are obliged to explain how the testimony came to be uttered in spite of its falsity, when rejecting testimonial premises. I call this methodological scruple Paley’s Principle. Following some initial clarifications, I explore various possible strengths and scopes of its claimed obligation, in order to determine whether a plausible version can be recovered. It is neither a logical norm nor a purely prudential principle. But relative to some socio-epistemic aims of argumentation, Paley’s Principle expresses a reasonable norm, though perhaps not in quite the way Paley intended it.